2014
DOI: 10.5858/arpa.2012-0541-oa
|View full text |Cite
|
Sign up to set email alerts
|

Luminal Subtypes Predict Improved Survival Following Central Nervous System Metastasis in Patients With Surgically Managed Metastatic Breast Carcinoma

Abstract: Context.-Metastatic breast cancer to the central nervous system (CNS) is second only to lung cancer metastasis to the CNS in frequency. Patients with triple-negative primary breast cancer and those with human epidermal growth factor receptor 2 (HER2)-positive primary breast cancer are at an increased risk for metastasis. Very little is known about predictive or prognostic variables once patients develop CNS metastases. Currently, therapeutic options are limited, with surgery generally offered primarily to thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Data from single institution experiences and prospective studies have yielded varying results. Triple-negative subtype seems to be associated with a poorer prognosis . Other sociodemographic and clinical predictors of outcome, on a population level, have not been well characterized.…”
Section: Introductionmentioning
confidence: 95%
“…Data from single institution experiences and prospective studies have yielded varying results. Triple-negative subtype seems to be associated with a poorer prognosis . Other sociodemographic and clinical predictors of outcome, on a population level, have not been well characterized.…”
Section: Introductionmentioning
confidence: 95%
“…HER2 expression in tumor cells was categorized according to the definition of Wolff et al [14]. The MIB-1 labeling index of stroma-invasive tumor cells was calculated in 500 or more tumor cells in 1 high-power field (hot spot) within the invasive tumor area and was set at a threshold of 14% [15]. The MIB-1 labeling index of blood vessel tumor emboli was calculated for positive tumor cells among all the tumor cells forming the blood vessel tumor emboli.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…We determined a higher cutoff age value (50 years), which remained significant in the multivariate analysis model. Patients with the TN subtype are reported to have the shortest interval between BC and CNSm and are considered to have the worst prognosis 21 ; in the current study, patients with CNSm arising from the TN subtype had the worst MOS. Surprisingly, we observed that patients with the LumA subtype had a shorter MOS compared with those reported in other studies, which might be due to the high frequency of NM in the current study.…”
Section: Discussionmentioning
confidence: 57%